PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN (Studi Pada Pengguna Aplikasi Gojek Tahun 2021) - Yolanda Frisia Sibarani; Joan Yuliana Hutapea (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This study was conducted to determine the effect of service quality and price on customer satisfaction for Gojek application users in 2021. The method of this study is a quantitative study, using questionnaire as the instruments. The sampling techniques is a non-probability sampling, the population in this study are the customers who uses Gojek application, with the number of samples 200. Which was taken on certain period of time. The analysis used is descriptive statistical analysis, correlation coefficient test, coefficient of determination test, F significant test, t significant test and multiple linear regression analysis. The results showed thatpartially there was a positive and significant effect between service quality on customer satisfaction, as well as price on customer satisfaction and simultaneously found a significant and positive effect between service quality and price on customersatisfaction.